Implementasi Media Film Berbasis Sejarah dalam Pembelajaran Sejarah Kebudayaan Islam di MTs YLPI Mujahiddin Kec. Pinggir - Mahesa, Rahman; Mario Kasduri (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
Islamic religious education encompasses several key components that serve as its primary objectives, including monotheism, noble morals, knowledge, and social life. These fundamental concepts are integrated into an educational framework that produces various subjects rooted in Islamic teachings, such as fiqh, aqidah akhlak, and the history of Islamic culture. This research aims to analyze the strategies employed by educators in implementing film media as a learning tool in the History of Islamic Culture subject at MTs YLPI Mujahiddin, Pinggir District. This study adopts a qualitative descriptive approach, utilizing interviews, observations, and documentation as data collection techniques. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that film media has been effectively integrated as a strategy to enhance students’ interest and engagement in learning. Educators utilize film media not only as an instructional tool but also as a means to create an interactive and immersive learning experience. This research serves as an evaluative measure to assess the effectiveness of film-based learning strategies in improving students' motivation and interest in the History of Islamic Culture subject at MTs YLPI Mujahiddin, Pinggir District.